Efeito da lectina de Dioclea violacea na lesão renal aguda induzida pela gentamicina - Leme, Ala Moana [UNIFESP] (2019)
Acute kidney injury (AKI) is characterized by the abrupt decline in glomerular filtration rate (GFR) that can be caused by sepsis, burn, hemorrhage or nephrotoxic substances such as the aminoglycoside gentamicin (Genta) antibiotic. Nephrotoxic AKI associated with these antimicrobials makes them restricted to the hospital environment. Thus, the search for treatments that prevent AKI is still necessary. Lectin extracted from the Fabaceae family plant, Dioclea violacea (DVL) is a protein of plant origin that has already had nephroprotective actions in ischemic AKI. Therefore, this study aims to evaluate the effect of DVL on gentamicin-induced acute kidney injury. Wistar rats were separated into control (CTL), Gentamicin (Genta, 40 mg/kg weight), Dioclea violacea (DVL, 0.1 mg/kg) and Gentamicin+Dioclea violacea (Genta+DVL) groups for 15 consecutive days. At the end of the experimental period, animals were weighed, 24-hour serum and urine samples collected, animal kidneys taken for creatinine analysis, proteinuria, creatinine clearance, urine sodium excretion, renal blood flow (RBF) and renal vascular resistance (RVR). Genta induced an increase in urinary volume (19,8 ± 1,77 ml), proteinuria (14,51 ± 1,73 mg/24h) and sodium (0,015 ± 0,00 %), while the Genta group + DVL (urinary volume: 14,20 ± 0,58 ml; proteinuria: 7,86 ± 0,87 mg/24h; sodium: 0,008 ± 0,00 %) did not show this increase. In renal function analysis, Genta induced increase in plasma creatinine (0,93 ± 0,09 mg/dl) compared to control ((0,58 ± 0,02 mg/dl) and this increase persisted in the Genta+DVL group 0,76 ± 0,05 mg/dl). The tubular lesion, marked by NGAL expression, showed that in the Genta group (4,3 ± 0,3 %) there was an increase compared to CTL ((0,40 ± 0,3 %) and this increase was reversed in the Genta+DVL group. (0,49 ± 0,04 %). The Genta group showed an increase in RVR ((310,21 ± 155,11 mmHg/ml) and a decrease in (RBF 5,90 ± 2,95 ml/min ml/min). However, treatment with DVL reversed both (RVR: 70,88 ± 35,44 mmHg/ml; (RBF: 22,05 ± 11,03 ml/min ml/min). For oxidative stress analysis, the Genta group showed an increase in lipid peroxidation via FOX-2 and TBARS when compared to CTL, however DVL reversed these effects. The results of this work suggest that DVL may at least partially prevent the effects of gentamicin and may be used as an aid in the prevention of nephrotoxic AKI.